The Geopolitical and Religious Conditions of the Arabian Peninsula Prior to the Prophethood of Muhammad SAW: an Anthropological and Historical Perspective - Yudi Imana; Engkos Kosasih; Muhammad Al Mighwar; Hüseyin Çaksen; Ibrahim Alhaji Isa (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study examines the condition of Arab society during the time of the Prophet Muhammad PBUH with a focus on social, political, economic, cultural, and religious aspects. Through a historical-sociological approach, this study aims to analyze the characteristics, structure, and dynamics of pre-Islamic Arab society to the early period of Islamic development. The research method used is a literature study by analyzing primary and secondary sources about the history of Arab society. The results of the study show that pre-Islamic Arab societies had a social structure based on a tribal system (qabilah) with values such as group solidarity ('asabiyyah), courage (muru'ah), and generosity (karam). Politically, there is no central authority that binds the entire Arabian peninsula, but rather is divided into autonomous tribal powers. Economically, Arab society relied on limited trade, livestock, and agriculture, with Mecca being an important trading center. In the religious aspect, the majority of Arabs adhere to polytheism, although there are also Jewish, Christian, and hanif (monotheistic) communities. The transformation of Arab society through the da'wah of the Prophet Muhammad (PBUH) took place gradually, with fundamental changes in the value system, social structure, law, and culture. This research contributes to a comprehensive understanding of the sociohistorical context of the emergence of Islam and the resulting societal transformation.